Therapeutic drug monitoring of anti-TNF drugs: an overview of applicability in daily clinical practice in the era of treatment with biologics in juvenile idiopathic arthritis (JIA) - A. Nassar-Sheikh Rashid; D. Schonenberg-Meinema; S. C. Bergkamp; S. Bakhlakh; A. de Vries; T. Rispens; T. W. Kuijpers; G. Wolbink; J. M. van den Berg (BMC, 2021)
Abstract Background Anti-tumor necrosis factor (TNF) drugs have improved the prognosis for juvenile idiopathic arthritis (JIA) significantly. However, evidence for individual treatment decisions based on serum anti-TNF drug levels and the presence of anti-drug antibodies (ADAbs) in children is scarce. We aimed to assess if anti-TNF drug levels and/or ADAbs influenced physician's treatment decisions in children with JIA. Methods Patients' records in our center were retrospectively screened for measurements of anti-TNF drug levels and ADAbs in children with JIA using etanercept, adalimumab or infliximab. Clinical characteristics and disease activity were retrieved from patient charts. Results We analyzed 142 measurements of anti-TNF drug levels in 65 children with JIA. Of these, ninety-seven (68.3%) were trough concentrations. N = 14/97 (14.4%) of these showed trough concentrations within the therapeutic drug range known for adults with RA and IBD. ADAbs against adalimumab were detected in seven patients and against infliximab in one patient. Seven (87,5%) of these ADAb-positive patients had non-detectable drug levels. A flowchart was made on decisions including rational dose escalation, stopping treatment in the presence of ADAbs and undetectable drug levels, showing that 45% of measurements influenced treatment decisions, which concerned 65% of patients (n = 42/65). Conclusions In the majority of patients, measurement of anti-TNF drug levels led to changes in treatment. A wide variation of anti-TNF drug levels was found possibly due to differences in drug clearance in different age groups. There is need for determination of therapeutic drug ranges and pharmacokinetic curves for anti-TNF and other biologics in children with JIA.